Леонід Соловйов як дослідник історії Херсона другої половини ХІХ ст. - Кібець, В. (Місто: історія, культура, суспільство, 2016)
Перед сучасною українською історичною наукою стоїть багато завдань, які потребують наукового вирішення. Серед них вивчення життя і діяльності видатних особистостей та історії окремих регіонів України займають не останнє місце. Стаття є спробою показати особливості дореволюційного минулого міста Херсона з позиції корінного жителя і мемуариста Л. П. Соловйова. Перед современной украинской исторической наукой стоит много задач, требующих научного решения. Среди них изучение жизни и деятельности выдающихся личностей и истории отдельных регионов Украины занимают не последнее место. Статья является попыткой показать особенности дореволюционного прошлого города Херсона с позиции коренного жителя и мемуариста Л. П. Соловйова. Modern Ukrainian historical science faces with many challenges that require a scientific solution. Exploring the life and work of famous people and history of individual regions of Ukraine are among them. The end of 19th - the beginning of 20th centuries in the history of Ukraine is characterized by a general revolutionary exaltation that was caused by sharp contradictions, national oppression, political disenfranchisement of the population. It is a time when new creators of history enter the political scene. Nowadays the important task is to rethink the role of the individual in history, to explore creative people, to fill the historical process with energetic, working people, to make this process anthropocentric. It is necessary not only to revive the forgotten names, but to determine a place for each personality in the history of Ukraine. The aim of the article is to show the features of the pre-revolutionary past of Kherson city from the perspective of Leonid Solovyov, indigenous inhabitant, engineer, qualified worker of Kherson sea port and brilliant memoirist.